Asynchronitäten der deutsch-deutschen Frauenbewegung - Young, Brigitte (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1994)
This article problematizes the much used cliche that Warnen are the main losers of German unification« and suggests that the »disempowerment« of warnen during and after Unification is due to two non-synchronization processes. First, the development of separate East and West German feminist identities has made it difficult for feminists to agree on common goals and strategies, and second, the state centered strategies of feminists fail to take into account the structural transformations of the German state.